A Study on the Literacy Rate of Buddhist Monks in Dunhuang during the Late Tang, Five Dynasties, and Early Song Period - Wu, Shaowei (Religions, 2022)
Among the Dunhuang documents, when examining some of the monk signature lists, name list of monks copying scriptures and name list of monks chanting scriptures in monasteries, we can estimate a relatively accurate literacy rate of the Buddhist sangha. Generally speaking, the literacy rate of the sangha during the Guiyi Army 歸義軍 period (851–1036) was lower than that during the Tibetan occupation period (786–851). The reason for this change is closely related to each regime’s Buddhist policy, the size and living situation of the sangha, and the Buddhist atmosphere. The decrease in the literacy rate of the sangha had great negative consequences, but when viewed under the context of the stay at home monks and the secularization of Buddhism, the number of literate monks had actually increased. They were more closely integrated with the secular society and their functions in the regional society were more pronounced. At the same time, the changes in the literacy rate of the monks in Dunhuang can also serve as an important reference for understanding the development of Buddhism in the Central China.